Sedentary behavior reduction and blood lipids in adults with metabolic syndrome: a 6-month randomized controlled trial - Ylinen, Venla P.; Sjöros, Tanja; Laine, Saara; Garthwaite, Taru; Norh,a Jooa; Vähä-Ypyä, Henri; Löyttyniemi, Eliisa; Houttu, Noora; Laitinen, Kirsi; Kalliokoski, Kari K.; Sievänen, Harri; Vasankari, Tommi; et al. (Springer Nature, 2025)
The aim of this study was to investigate whether a reduction in accelerometer-measured sedentary behavior (SB) improves blood lipids in inactive adults with metabolic syndrome (MetS). Sixty-four participants were randomly assigned into intervention (INT, n = 33) and control (CONT, n = 31) groups. The INT group was instructed to reduce SB by 1 h/day without increasing formal exercise, whereas the CONT group was advised to maintain usual SB habits. SB and physical activity (PA) were measured with accelerometers throughout the intervention. Plasma lipid concentrations and dietary intake by food diaries were assessed at baseline and at the end of the intervention. High-density lipoprotein percentage of total cholesterol decreased during the intervention similarly in both groups (p = 0.047). Other blood lipids did not change from baseline to six months in either group. The CONT group had a statistically significant reduction in the intake of saturated fatty acids compared to the INT group (p = 0.03). Intervention resulting in a 40-minute reduction in daily SB and 20-minute increase in habitual MVPA seems to not be effective in improving blood lipids in adults with MetS. Reducing SB together with a higher volume and/or intensity of PA and proper nutrition may be needed to reduce the risk of cardiometabolic diseases. Trial registration. This study is registered at ClinicalTrials.gov (NCT03101228, 05/04/2017).